Raman spectroscopy of M3B7O13X boracites (M = Cr, Co, Ni, Cu, Zn, Cd; X = Cl, Br, I). (3rd March 2014) - Iliev, Milko N.; Schmid, Hans
<x xml:space="preserve">Abstract</x> We report results of a Raman study on single crystals of 16 boracites M3B7O13X (M = Cr, Co, Ni, Cu, Zn, Cd; X = Cl, Br, I) over a broad temperature range. The Raman modes for all boracites in their high‐temperature prototype cubic (F<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg55mvhsd1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />4¯</alternatives>3c) phase are compared. With decreasing temperature, most (but not all) compounds present a transition to the low‐temperature orthorhombic phase (Pca21) or to a sequence of orthorhombic, monoclinic (Pa), and trigonal (R3c) phases. The variations of the Raman spectra through different phases are studied in detail. Special attention is paid to the temperature hysteresis near the transitions and the dependence of transition temperature on the direction of crystal growth for the same material. Copyright © 2014 John Wiley & Sons, Ltd.